The economics and political economy of transportation security - Button, Kenneth John 1948- (Edward Elgar Publishing, 2016)
In this clear and observant book, Kenneth Button provides an overview of the economics and political economy of transport security, considering its policy from an economic perspective. His analysis applies micro-economic theory to transport issues, supporting and enhancing the larger framework of our knowledge about personal, industrial, and national security
Keywords: Transportation--Security measures; Sicherheit; Politische Ökonomie; Transport